PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN, PERTUMBUHAN, DAN NILAI PASAR PERUSAHAAN (Studi Empiris pada Perusahaann Konstruksi, Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2012) - Maria Carolin Oktavia; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
This study aimed to examine the influence of Intellectual capital to the financial performance of the company. This study is done because of the awareness that IC is an importance component that can create value added and competitive advantage for the companies. The population in this study consists of construction, property & real estate firms in Indonesia Stock Exchange in year 2009-2012. Sampling method is used purposive sampling. With one of the criteria that the company did not have a negative net income and not delisting during observation, so the samples consists of 88 companies. This study uses a method developed by Pulic (1998) - Value Added Intellectual Coefficient (VAIC). This study examine the influence VAIC and its components (capital employed (CEE), human capital (HCE) and structural capital (SCE)) towards the company's financial performance (Return on Assets, Return on Equity, Revenue Growth, Employee Productivity, and Earning per share). Partial Least Square (PLS) that used to test the influence of VAIC financial performance of the company.The results of this study indicate that there is a positive and significant relationship between VAIC to financial and VAIC to market value performance. Relationship between VAIC and growth is not significant. Last year VAIC does not affect to financial, growth, and market value performance in current year.